Assessing the Validity of Adult-derived Prognostic Models for Primary Sclerosing Cholangitis Outcomes in Children. Issue 1 (January 2020) - Deneau, Mark R.; Valentino, Pamela L.; Mack, Cara; Alqoaer, Khaled; Amin, Mansi; Amir, Achiya Z.; Aumar, Madeleine; Auth, Marcus; Broderick, Annemarie; DiGuglielmo, Matthew; Draijer, Laura G.; El-Matary, Wael; et al.
ABSTRACT: Background: Natural history models for primary sclerosing cholangitis (PSC) are derived from adult patient data, but have never been validated in children. It is unclear how accurate such models are for children with PSC. Methods: We utilized the pediatric PSC consortium database to assess the Revised Mayo Clinic, Amsterdam-Oxford, and Boberg models. We calculated the risk stratum and predicted survival for each patient within each model using patient data at PSC diagnosis, and compared it with observed survival. We evaluated model fit using the c-statistic. Results: Model fit was good at 1 year (c-statistics 0.93, 0.87, 0.82) and fair at 10 years (0.78, 0.75, 0.69) in the Mayo, Boberg, and Amsterdam-Oxford models, respectively. The Mayo model correctly classified most children as low risk, whereas the Amsterdam-Oxford model incorrectly classified most as high risk. All of the models underestimated survival of patients classified as high risk. Albumin, bilirubin, AST, and platelets were most associated with outcomes. Autoimmune hepatitis was more prevalent in higher risk groups, and over-weighting of AST in these patients accounted for the observed versus predicted survival discrepancy. Conclusions: All 3 models offered good short-term discrimination of outcomes but only fair long-term discrimination. None of the models account for the high prevalence of features of autoimmune hepatitis overlap in children and the associated elevated aminotransferases. A pediatric-specific model is needed. AST, bilirubin, albumin, and platelets will be important predictors, but must be weighted to account for the unique features of PSC in children. Abstract : Supplemental Digital Content is available in the text